Penguatan Pendidikan Karakter dan Literasi Anak Melalui Kegiatan Mendongeng dan Membaca Nyaring - Diah Siti Utari; Merin Nevyrasari; Tengku Norlizawati; Riau Sujarwani (Universitas Negeri Gorontalo, 2025)
Limited access to literacy and the lack of engaging educational approaches pose persistent challenges in fulfilling children's rights to access appropriate information. This community service program aimed to provide a child-friendly literacy space and encourage children’s confidence in expression through storytelling and read-aloud activities. The initiative was a collaborative effort between Forum PUSPA Hamidah and TBM Kuntum Mekar in Tanjungpinang, utilizing a community-based educational approach. The implementation consisted of planning, execution, evaluation, and publication stages. A total of 19 children aged 5–12 participated in the interactive storytelling and read-aloud sessions. Evaluation was conducted using a descriptive-qualitative method through observation, participant reflection, and informal interviews with parents. The results showed increased active participation, improved confidence in public speaking, and deeper understanding of moral values such as empathy, cooperation, and compassion. This program contributed significantly to fostering early literacy habits, strengthening the role of TBM as a non-formal learning space, and offering a replicable collaborative model for similar communities.